THE ANALYZING OF MATHEMATICS LEARNING DIFFICULTIES IN 3RD GRADE STUDENTS OF SD NEGERI SEMAMPIR 01, BATANG DISTRICT - Nora Wahyu Kusuma Dewi; Riris Setyo Sundari; Sukamto Sukamto (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
Abstract, This study aims to reveal the difficulties of learning mathematics students in calculating multiplication operation material and the factors that influence the learning difficulties of students in 3rd grade students of SD Negeri Semampir 01, Batang district. The type of this research is a descriptive qualitative approach. The research subjects were all student of 3rd grades of SD Negeri Semampir 01, with the total of 22 students, consisting of 12 male students and 10 female students and 3rd grade teachers as the informants. The collecting data technique of from informants are use observation, interviews, questionnaires, and documentation technique. The results that obtained in this study are presented as follows: (a)The mathematics learning difficulties in the multiplication operations included difficulties in understanding concepts (84.05%), difficulties in learning skills (75.42%), and difficulties in determining the values of place (65.85%). (b)The factors that influence the difficulties of mathematics learning in the material of multiplication operations are include attitudes in learning (54.5%), body health (31.75%), sensing ability (4.5%), motivation (72.7%) ), school environment (49.95%).Keyword: Learning Difficulties, Mathematics, Multiplication